The isomeric ratios in ¹⁰⁷Ag(γ, n)¹⁰⁶ᵐ,ᵍAg photonuclear reaction induced in the giant dipole resonance region - Tran , Duc Thiep; Truong , Thi An; Phan , Viet Cuong; Nguyen , The Vinh; Bui , Minh Hue; A. , G. Belov; O. , D. Maslov (Nuclear Science and Technology, 2013)
We measured for the first time the isomeric ratios in 107Ag(γ, n)106m,gAg photonuclear reaction by using the activation method and γ-ray spectroscopic method for the whole giant dipole resonance (GDR) region. The high-purity natural Ag foils in disc shape were irradiated with bremsstrahlungs generated from an electron accelerator Microtron. The induced gamma spectra in the irradiated foils were measured by the high resolution γ-ray spectroscopic system which consists of a high-purity Germanium detector and a multichannel analyzer. In order to improve the accuracy of the experimental results the necessary corrections were made in the γ-ray activity measurements and data analysis. The results were analyzed, discussed and compared with those of other authors. For the mentioned reaction, the isomeric ratios in the energy range from 14 to 24 MeV bremsstrahlungs in this work (except the values at 14, 18 and 20) are new measurements.